Validação na prática clínica do protocolo de acolhimento com classificação de risco em pediatria - Magalhães, Fernanda Jorge (2016)
The Host with Risk Rating (HRR) refers to the act of receiving with active listening and determine the patient care priority in urgency/emergency. For this, the nurse uses the Host Agreement with Risk Rating in Pediatrics as an instrument that classifies patients into five priority service using colors (red, orange, yellow, green and blue). This study aimed to validate the 2rd Edition of the HRR protocol in Pediatrics in clinical practice urgent / emergency. Methodological study in pediatric hospital in the city of Fortaleza-CE-Brazil. Developed in four stages: 1) training course for the preparation of the 1st version of the 2nd edition of the HRR in Pediatrics; 2) validation of content and appearance by expert judges on the 3rd edition of the Protocol; 3) interrater reliability of two classifiers interobserver trained nurses (CITN) and the researcher and two nurses classifiers interobserver untrained (CINTN) and the researcher who, each evaluated 100 children and / or adolescents at different times, totaling 400 ratings; and 4) application and validation in clinical practice protocol, conducted by researcher with 200 children and/or adolescents. The data analyzed using SPSS-21, using the Kappa coefficient with a confidence interval (CI) of 95% and the ratio of Chance. Study approved by the Research Ethics Committee under Opinion No. 1,282,924. The results showed: a concordance of over 80% among expert judges as simplicity, clarity, relevance of content, appearance and technical applicability of the 2nd Protocol Edition. In the inter-rater reliability of stage, it was found: prevalence of 80.0% of patients classified as less urgent (green 50.7%) and non-urgent (blue 29.3%); It revealed a substantial excellent agreement between the nurses and the researcher with a Kappa between 0.62 and 1.0. As for ECIT-2 and the researcher gave excellent agreement (kappa 1.0); excellent agreement between ECINT-2 and the researcher (Kappa 0.887) and between ECIT-1 and the researcher (Kappa 0.725) and also a substantial agreement between the ECINT-1 and the researcher (Kappa 0.619). As the odds ratio was found that clinical discriminators identified in the study have a higher chance of being classified as less urgent (green) or not urgent (blue). In the application stage showed higher frequency of changes in vital signs (24.5%) and respiratory disorders (20.5%) and clinical discriminators, the majority (57.5%) patients were assessed as pain and without 45.0 % classified as blue. The average time for the rating was 1.5 minutes and medical care was 35.7 minutes, corresponding adjustment to the profile of the population served. It was concluded that the HRR Protocol in Pediatrics is a health technology that presented interrater reliability of trained classifiers nurses not trained together with the researcher and that is valid in clinical practice in order to direct the nurse in the risk classification in situations urgent / pediatric emergency.